HUBUNGAN LINGKAR PINGGANG DENGAN KEJADIAN HIPERTENSI PADA PETANI DI WILAYAH KERJA PUSKESMAS BASALA KABUPATEN KONAWE SELATAN - Harleli Harleli (NHM PRESS, 2022)
Waist circumference is anthropometric measurement that describes central obesity. The prevalence of central obesity continues to increase in the world, including Indonesia. The increase in the incidence of central obesity has an effect on the increase in various diseases including hypertension, data from the Basala Community Health Center. during the last 3 years, hypertension has always been in the second rank of the top ten diseases. This study aims to determine the relationship between waist circumference with incidence of hypertension in the work area of ​​Basalah Community Health Center, South Konawe Regency in 2020. This study used an observational study with a cross sectional design and the sampling technique used purposive sampling. The population used was all farmers aged 36 - 64 years as many as 3058 people and a sample of 209 people. The research sample used the stratified random sampling method. Of the 209 respondents, there were 88 respondents with normal waist circumference and abnormal waist circumference as many as 121 people.The results of statistical analysis using the chi-square statistical test showed that there was no significant relationship between waist circumference with incidence of hypertension among farmers in the work area of ​​Basalah Community Health Center, South Konawe Regency in 2020. (p value = 0.651). The conclusion is that there is no relationship between waist circumference with the incidence of hypertension in farmers. It is recommended that people maintain a balanced nutritional intake so that they are avoided from various degenerative diseases such as hypertension.